Implementation of Zoning System Policy in New Student Admission as an Effort to Equalize Education in Indonesia - Meirinawati; Indah Prabawati; Eva Fanida; Galih Pradana; Revienda Fitrie (Technium Social Sciences Journal, 2023)
Education is a right for everyone. The problem that still occurs is the lack of equitable facilities and infrastructure to support education. One of the government’s efforts to accelerate education equality is the establishment of a zoning policy through Minister of Education and Culture Regulation No. 14/2018 on New Student Admission. To measure the success of a policy implementation, this phenomenon will be analyzed using Edward III’s policy implementation model. Edward III’s theory is considered relevant to the analysis process for research with a qualitative approach. The purpose of this research is to see and describe the phenomena that occur in the implementation of the zoning system policy in the admission of new students as an effort to equalize Indonesian education. By using indicators of communication, resources, organizational structure, and attitudes or dispositions. This research shows the results of the implementation of the zoning system policy in PPDB which is quite good as an effort to equalize education in Indonesia.